Criminal Confrontation with the Phenomenon of Sexual Harassment against Working Women - Khalfa, Samir (Journal of Legal Studies and Researches, 2021)
The phenomenon of sexual harassment is the scourge of the age and an actual crisis for women and one of the most important outstanding issues that Algerian working women suffer, especially in silence. In order to put an end to the growth and spread of this scourge, the Algerian legislator was keen to provide it with the necessary legal protection by criminalizing these phenomena and introducing a series of amendments to strengthen the criminal protection of harassed women, according to Article 341 bis of the Algerian Penal Code.